2017
DOI: 10.1186/s13287-016-0458-1
|View full text |Cite|
|
Sign up to set email alerts
|

Study of the reparative effects of menstrual-derived stem cells on premature ovarian failure in mice

Abstract: BackgroundYoung female patients who receive chemotherapy frequently face premature ovarian failure (POF). The therapeutic potential of stem cells in these patients has been explored in stem cells derived from different sources. However, many of these types of stem cells are either difficult to obtain or obtaining them involves invasive procedures. Here, we show that menstrual-derived stem cells (MenSCs) are easy to access and exhibit mesenchymal stem cell-like properties. MenSCs are therefore a novel source of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
144
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 155 publications
(155 citation statements)
references
References 51 publications
10
144
0
1
Order By: Relevance
“…A week after the injection of busulfan, histological analyses clearly showed that the number of follicles at different stages of development, especially early antral and preovulatory, were reduced, and follicles exhibited poor development and maturity. This result is consistent with that of Wang et al (Wang et al, ). Chemotherapy induced fibrosis formation in ovarian stroma has also been reported, which is similar to the findings of our study (Sun et al, ; Wang et al, ).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…A week after the injection of busulfan, histological analyses clearly showed that the number of follicles at different stages of development, especially early antral and preovulatory, were reduced, and follicles exhibited poor development and maturity. This result is consistent with that of Wang et al (Wang et al, ). Chemotherapy induced fibrosis formation in ovarian stroma has also been reported, which is similar to the findings of our study (Sun et al, ; Wang et al, ).…”
Section: Discussionsupporting
confidence: 94%
“…GCs of follicles which surround oocytes play a vital role in the development of follicles through secretion of growth factors and hormones (Chavakis, Urbich, & Dimmeler, ; Iorio et al, ). Damage to GCs can thus impair growth, development and survival of oocytes (Wang et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Other members of the lectican PG family do not contain this KS-rich region. [60] The high density of the CS chains in aggrecan provide a high fixed charge density critical to the performance of aggrecan in water imbibition, tissue swelling, and the generation of internal hydrostatic pressure in weight bearing tissues. [6,59] A comparative study of CS and HS in the promotion of 3D chondrogenesis of mesenchymal stem cells (MSCs) showed that CS-hydrogels of low mechanical stiffness provide a scaffold which promotes MSC-based cartilage tissue regeneration.…”
Section: Aggrecan Structure and Functionmentioning
confidence: 99%
“…The original article [1] contains errors in Figs. 3i, j and 5e whereby the first column of each sub-panel is incorrectly labelled as having used GFP-staining; instead, the images were generated using TUNEL assays.
Fig.
…”
Section: Erratummentioning
confidence: 99%